GROWTH OF Chlamydomonas sp. AS A PRELIMINARY STEP ON THE METAL TOXICITY TESTING - Yoshua Nobel Siahaan; Budijono Budijono; Dwi Hindarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT             This study is aimed to learn the capabilities of Chlamydomonas sp. as biota qualifies for metal toxicity test. This research is done for 17 days by seeing an entire living phase of Chlamydomonas sp. in the growth curve. A cell density analysis from Chlamydomonas sp. calculated using a microscope.This result indicate that there are 4 living phases of Chlamydomonas sp. it’s composed of phases lag, an exponential phase, stationary phases and phases leading to death. Chlamydomonas sp. qualified as a test biota for a heavy metal toxicity test using phytoplankton according to Asean-Canada Cooperative Programme on Marine Science Phase II. This is seen from the growth of cell density that exceeds the minimum limit on the 4th day of inoculation growth curve or at the beginning of an exponential phase with density of cell 3,68 x 104 cell.mL-1.Kata Kunci : Phytoplankton, Chlamydomonas sp., Toxicity test